(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Rhinoscleroma (RS) is a chronic granulomatous disease caused by Klebsiella rhinoscleromatis. In all the patients, the nose is affected but sometimes extends to any parts of the airways. Diagnosis of this disease is done on the basis of the histopathological examination or direct evidence of the bacteria in nasal exudates. The differential diagnoses of the RS are syphilis, malignancy and midline granuloma. Streptomycin is drug of choice, although fluoroquinolones and cephalosporin also provide good results. Surgery is opted in case of obstruction or deformity. Here, we reported a case of 11-year girl diagnosed as RS on the basis of the histopathological examination. This case was treated by endoscopic removal of the mass in the nasal cavity followed by a course of ciprofloxacin. She was found asymptomatic at the last visit of 1 year after treatment and there was no evidence of recurrence.